Investigation of gate induced noise in E‐mode GaN MOS‐HEMT and its effect on noise parameters. (8th January 2018) - Panda, D.K.; Lenka, T.R.
Abstract: In this paper, the effects of gate induced noise for a gate recessed enhancement‐mode GaN‐based metal‐oxide‐semiconductor high electron mobility transistor (MOS‐HEMT) is investigated. To analyze this, a surface potential–based compact model for gate induced noise is developed. The model is validated by comparing with TCAD device simulation results as well as with the available experimental data of GaN HEMT and MOS‐HEMT having different gate lengths and widths from the literature. With the help of the developed model, the effect of oxide thickness on different noise sources is investigated by considering all high‐frequency noise sources including the shot noise resulted from gate leakage current. The effects of gate leakage current on different technology dependent parameters such as oxide thickness and gate length are also investigated. A 2‐port noise equivalent circuit for GaN MOS‐HEMT is designed by considering all high‐frequency noise sources. The different noise parameter models are developed from the Y parameters of the 2‐port noise equivalent circuit and compared with available experimental data of GaN HEMT and MOS‐HEMT from literature. The impact of gate induced noise on all noise parameters is also investigated.